Reponse d'une luzerne (Medicago sativa) a la fertilisation phosphatee et a l'inoculation avec des champignons mycorhiziens a vesicules et arbuscules dans un Vertisol deficient en P - Mamo, T.; Haque, I. (1986)
Asesses the role of Vesicular Arbuscular Mycorrhizal fungus in Lucerne mineral nutrition, and the response of phosphate fertilization to Lucerne.